Using virtual reality treadmill as a locomotion technique in a navigation task: Impact on user experience – case of the KatWalk - Cherni, Heni; Nicolas, Souliman; Métayer, Natacha (International Journal of Virtual Reality, 2021)
This paper reports empirical results from a study on the impact of the KatWalk virtual reality omnidirectional treadmill on the user experience. The omnidirectional treadmill is a mechanical device, that allows the user to perform locomotive motion in any direction, allowing for 360 degrees of horizontal movement. This locomotion method appeared as a potential solution of the locomotion problem in virtual reality after the emergence and the democratization of the new generation of head-mounted display systems such as HTC Vive and Oculus Rit. However, little empirical work has been done to test the efficiency of the tool as a locomotion technique in virtual environments. Twenty-four subjects (13 females, mean age = 30.38, SD = 6.32) participated in the experiment. Results showed that the tool is suitable for traveling in virtual environments seen through head-mounted display systems, whether they are composed of plan or bumpy ground, with or without obstacles.